Dynamics of global institutional collaboration in insect taxonomy reveal imbalance of taxonomic effort. Issue 1 (11th April 2018) - Deng, Jun; Wang, Xu; Zeng, Lingda; Zou, Xuting; Huang, Xiaolei
Abstract: Institutional collaboration promotes development and technical advances in science. A social network analysis is often used to assess the evolutionary dynamics of institutional collaboration in many fields. However, there has been no social network analysis of the insect taxonomy field based on bibliometric data. To explore the evolutionary pattern of institutional collaboration in this field, a total of 21 095 articles were collected from the Web of Science between 1997 and 2016. According to author affiliations data, we found increasingly closer collaboration has occurred in this network over time. Due to economic development, social attention, and policies supporting science and research, developing countries such as China and Brazil have shown a strong upward tendency towards collaboration since 2001. However, the development of institutional collaboration reveals imbalance of taxonomic effort and requires careful attention to certain aspects. Several countries have published numerous research articles, whereas most countries have published a small number of papers. Most institutions have tended to collaborate with institutions from same country, neighbouring countries or continent. Some institutions in developing countries (e.g. China) have numerous collaborators, however these institutions only played a modest role in introducing new collaboration between their collaborators. More work needs be done to improve intermediary ability and to reduce the influence of geographical distance. This study offered a vision for understanding the evolutionary dynamics of institutional collaboration in the insect taxonomy field, and it also suggested further enhancement of institutional collaboration in some weak aspects.